THE ROLE OF THE OLDER GENERATION IN FOSTERING A SENSE OF RESPECT FOR NATIONAL AND UNIVERSAL VALUES IN YOUNG PEOPLE - Akhmadiev Mayli Mukutdinovich; Ashboyev Akramjon Karimjonovich (Western European Studies, 2024)
This article widely covers the socio-philosophical factors in the formation of respect and loyalty to the national and universal values of the younger generation in the context of the modern process of globalization. In this process, the role and importance of representatives of the older generation was analyzed.
Keywords: youth and society; social development; the essence of values